(untitled) (Journal of Imam Al-Kadhim College, 2024)
It is obvious that the specialist of Islamic teams is accused before others by his contemporaries of bias to another thought and belief because when he started to look at these teams and boredom, his letters will count on him before his breath and therefore we find himself put himself in difficult labor and equation that comes out of it only with great luck, as we find that the researcher in this battle will receive him in case they seek a inclination or something of sympathy towards their belief or symbols and this is what we will find We are looking for Shahrastani in the circle of belief .